Indoor air quality in a preschool - Telejko, Marek (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The article presents the results of indoor air quality (IAQ) assessment in four local preschools. The natural ventilation system was used in the buildings. Outdoor air was supplied to the premises through a leak in the external walls and air intakes were of maximum efficiency of 30 m3/h. Parameters describing IAQ were measured, such as: temperature, relative humidity and carbon dioxide concentration. Two series of studies were performed in each preschool. On the basis of the survey, it can be clearly stated that the indoor air quality in preschools is considered to be very low very low. All the analyzed parameters describing the quality do not meet the current legal requirements. Reported values of CO2 concentration exceeded three times the value set of the recommended maximum.